Lead, Cadmium, Copper and Zinc Concenrations in Permanent Teeth in the Population of Southern Poland - Szostek, Krzysztof (Anthropological Review, 1992)
Lead, cadmium, copper and zinc concenrations in permanent teeth in the population of southern Poland were analysed by AAS technique. There was a statistically significant correlation between the quantities of heavy metals and the age of subjects. Also determined there were the sex differences and the relationship between the environmental conditions and the level of the accumulated heavy metals.